Is There Association Between Stress and Bruxism? A Systematic Review and Meta-Analysis - Chemelo, Victória dos Santos; Né, Yago Gecy de Sousa; Frazão, Deborah Ribeiro; Souza-Rodrigues, Renata Duarte de; Fagundes, Nathalia Carolina Fernandes; Magno, Marcela Baraúna; Silva, Cláudia Maria Tavares da; Maia, Lucianne Cople; Lima, Rafael Rodrigues (Frontiers in Neurology, 2020)
This systematic review and meta-analysis aimed to investigate a possible association between stress and bruxism in humans. This study was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines under the code CRD42020188862, and the searches were performed on the following databases: PubMed, Scopus, Web of Science, Cochrane, LILACS, OpenGrey and Google Scholar. This systematic review evaluated observational studies in adult humans with and without stress to verify the association between bruxism and the presence of stress. The risk of bias was evaluated through the Joanna Briggs Institute Critical Appraisal Tools for Analytical Cross-Sectional Studies. In quantitative analysis, the Odds Ratio (OR) and their 95% confidence interval (CI) were calculated through a fixed-effect model. Furthermore, a summary of the overall strength of evidence was presented using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE). A total of 1458 studies were identified, and six were included in this systematic review. Two studies included were classified with a low risk of bias, and the others were classified with a moderate risk of bias. In three articles, a meta-analysis was performed and showed an association between these two factors (OR 2.07 [1.51, 2.83], p<0.00001, I2 = 45 %). Besides that, the low certainty of the evidence was detected among this association. A low certainty of the evidence was detected among this association. Stressed individuals show a higher chance of presenting bruxism when compared to healthy individuals. Despite the low heterogeneity found in the quantitative analysis among the articles reporting an association between stress and bruxism, further studies with similar methods are necessary to understand this relationship better.